PENGARUH KUALITAS LAYANAN DAN BRAND IMAGE TERHADAP LOYALITAS NASABAH BMT MITRA PRUNUS SEJAHTERA KOTA TANGERANG - Edy Junaedi; Nurul Robiatin (Jurnal Asy-Syukriyyah, 2022)
The competitive conditions of Islamic financial institutions are getting tighter from time to time, so that every company must create a new marketing strategy to be able to maintain and gain a wider market share and increase customer loyalty. The purpose of this study is to determine whether service quality and brand image partially or simultaneously affect customer loyalty at BMT Mitra Prunus Sejahtera and to determine the most dominant variables have an effect. The data collection method was carried out through questionnaires distributed to BMT Mitra Prunus Sejahtera customers, with the criteria of having been a savings customer for one year and actively conducting savings transactions at least once a week. Samples were taken as many as 100 respondents of savings customers. The data obtained were then processed using SPSS version 22 and analyzed using multiple linear regression analysis. This analysis includes reliability test, validity test, multiple linear regression test, hypothesis testing through Ttest and Ftest as well as coefficient of determination (R2) and classical assumption test. T-test results show that service quality and brand image partially have a positive and significant effect on savings loyalty at BMT Mitra Prunus Sejahtera. The Ftest test shows that service quality and brand image simultaneously have a significant effect on savings loyalty at BMT Mitra Prunus Sejahtera with an effect of 60.9%, while the remaining 39.1% is influenced by other variables outside this model. The dominant influence is shown by the brand image variable, followed by the service quality variable.